EVIDENCE ON THE INFLUENCE OF ALTITUDE ON ALLERGIC SYMPTOMS IN CHILDREN - BAKER, JULIA (Instituto Politécnico Nacional, CD MEXICO, DF, MEX, 1977)
This is a preliminary study of the morphologic details, hitherto unrecognized, in Ammon's horn revealed by Achucarro's modification of the staining technique of Rio-Hortega
TEX REP BIOL MED
Keywords: ALTITUDE, ALLERGIC, SYMPTOMS, CHILDREN; MULTIDISCIPLINARIA; CIENCIAS CLINICAS; PATOLOGIA CLINICA